Treasury of Norse mythology : stories of intrigue, trickery, love, and revenge - Napoli, Donna Jo, 1948-; Balit, Christina (Washington, D.C. : National Geographic, 2015)
"Classic stories and dazzling illustrations of gods, goddesses, heroes and monsters come to life in a stunning tableau of Norse myths, including those of the thunder god Thor, the one-eyed god and Allfather Odin, and the trickster god Loki. The lyrical storytelling of award-winning author Donna Jo Napoli dramatizes the timeless tales of ancient Scandinavia. This book is the third in the trilogy that includes the popular National Geographic Treasury of Greek Mythology and National Geographic Treasury of Egyptian Mythology."-- ?c Provided by publisher.
Introduction -- Note on Norse Names -- Creation -- The Cosmos -- The Gods Clash -- Odin's Quest -- Loki's Monstrous Children -- Wagers & Treasures -- Shape-Shifters -- Heimdall's Many Children -- Freyja's Shame -- Thor's Hammer -- Thor the Greedy -- Idunn's Apples -- Skadi & Njord -- Frey & Gerd -- Death by Blunder -- The Gods Take Vengeance -- Kvasir's Enduring Poetry -- Destruction -- Afterword -- Map of the Ancient Norse World -- Time Lines of Norse History -- Cast of Characters -- Bibliography -- Index.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 8-12.
Vendor-supplied metadata.
Keywords: Mythology, Norse -- Juvenile literature; Gods, Norse -- Juvenile literature; Tales -- Scandinavia; JUVENILE NONFICTION / Social Science / Folklore & Mythology; Gods, Norse; Mythology, Norse; Tales; Scandinavia; Electronic books- OSLIS; Juvenile works; Electronic books